Composite microsphere adsorbent and preparation method thereof
By using composite microsphere adsorbents, the high cost, non-degradable and environmental pollution problems of existing adsorbent materials when dealing with heavy metal pollution are solved, and efficient, economical and environmentally friendly heavy metal adsorption effect is achieved.
Patent Information
- Application Number
- CN202411626775.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-11
AI Technical Summary
Existing adsorbent materials have high costs, non-degradability and environmental pollution when dealing with heavy metal pollution, which is difficult to meet the requirements of green chemistry.
Compound microsphere adsorbents are used, which are composed of cellulose, nanosilica, 4-vinylpyridine, etc., and are prepared by radiation graft modification technology to form an adsorbent with excellent heavy metal adsorption ability.
This adsorbent exhibits efficient, economical and environmentally friendly characteristics when adsorbing heavy metals, and is easy to degrade and will not cause pollution to the environment.
Smart Images

Figure CN119588318A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbent materials, and in particular to a composite microsphere adsorbent and a preparation method thereof. Background Art
[0002] The heavy metals contained in wastewater have significant biological toxicity and cannot be degraded by microorganisms in water bodies, so they need to be separated from water bodies. The current methods for treating heavy metal ions are: chemical precipitation, ion exchange, reverse osmosis, filtration, extraction, oxidation-reduction and adsorption. Compared with other methods, adsorption is the most economical and efficient method for treating metal ion pollution. It does not introduce other metal ions during the adsorption process, does not require additional energy input during the adsorption process, and can be separated promptly and effectively after adsorption, all of which meet the requirements of the currently advocated green chemistry. The most critical part of the adsorption method is to select an adsorbent with good adsorption performance, so the development and research of cheap and efficient new adsorption materials has become one of the hot topics for scientists.
[0003] There are many types of adsorbents at present, such as ion exchange resins, zeolites, activated clays, activated carbons, grafted modified polypropylene, polyethylene, etc. However, the substrates of the above adsorbents are usually chemical materials such as polyethylene and polypropylene, which are extremely difficult to degrade and cause great pollution to the ecological environment. Cellulose has the advantages of being cheap, degradable, and non-polluting to the ecological environment, so scientists have shifted their research targets to cellulose. Unmodified natural cellulose only contains hydroxyl groups, and its adsorption performance for metals is not ideal. Therefore, it is necessary to prepare adsorbent materials with excellent adsorption performance and great application prospects through functional modification and design.
[0004] Radiation grafting modification is an important means of material modification. This method can be carried out at room temperature, and the grafting rate is higher than that of conventional methods. In addition, the grafting rate of functional monomers on the substrate can be precisely controlled by controlling the irradiation conditions, such as dose, dose rate, etc., thereby obtaining functional materials with different properties. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art, the present invention aims to provide a composite microsphere adsorbent and a preparation method thereof. The prepared composite microsphere adsorbent has excellent heavy metal adsorption capacity and is environmentally friendly.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A composite microsphere adsorbent comprises, by weight, 1-1.1 parts of cellulose, 0.05-0.1 parts of a cross-linking agent, 1-2 parts of silicon dioxide, 8-10 parts of 4-vinylpyridine, 16 parts of NaOH, 24 parts of urea, 168 parts of water, 212 parts of methanol, 100 parts of an emulsifier and 2000 parts of liquid paraffin.
[0008] Preferably, the cross-linking agent is epichlorohydrin.
[0009] Preferably, the emulsifier is Span 80.
[0010] Preferably, the silicon dioxide is nano silicon dioxide.
[0011] The method for preparing the composite microsphere adsorbent comprises the following steps:
[0012] (1) 16 parts of NaOH and 24 parts of urea are dissolved in 160 parts of water and stirred to form a solution, which is then cooled to -15--9°C, cellulose and a cross-linking agent are added and stirred at 400 r / min for 30 min, and then centrifuged and degassed at 25°C and 5000 r / min for 30 min to obtain a transparent cellulose solution;
[0013] (2) adding an emulsifier and silicon dioxide to liquid paraffin and stirring the mixture ultrasonically to disperse the mixture uniformly, then adding the mixture to a transparent cellulose solution, stirring and emulsifying the mixture at 25° C. and 800 r / min for 3 h, and then adjusting the pH to 6.9-7.1 with dilute hydrochloric acid. After standing, the mixture is separated, the aqueous phase is filtered and washed twice with deionized water and acetone, and freeze-dried to obtain cellulose / silica microspheres;
[0014] (3) 12 parts of methanol and 8 parts of water were mixed and 4-vinylpyridine was added and stirred to form a solution, and cellulose / silica microspheres were added. The oxygen in the solution was purged with nitrogen, and the solution was sealed with vacuum paper and placed in a refrigerator to swell for 24 hours, and then sent to the cobalt source room for irradiation. After the irradiation, the sample was taken out, wrapped with filter paper and placed in a Soxhlet extractor, and 200 parts of methanol were added for extraction for 24 hours, and then filtered and dried to obtain a composite microsphere adsorbent.
[0015] Preferably, the concentration of dilute hydrochloric acid in step (2) is 0.1 mol / L.
[0016] Preferably, the freeze drying in step (2) is freeze drying at -50-45°C for 24 hours.
[0017] Preferably, the irradiation conditions in step (3) are a dose rate of 20 Gy / min and an absorbed dose of 20 kGy.
[0018] Preferably, the drying in step (3) is performed in a vacuum oven at 60° C. for 24 hours.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides a composite microsphere adsorbent and a preparation method thereof. Nano-silicon dioxide has good dispersibility and can prevent cellulose from agglomerating in the process of forming microspheres. In addition, the surface of nano-silicon dioxide particles is negatively charged and can form hydrogen bonds with hydrogen on the hydroxyl groups in cellulose, so that cellulose is adsorbed on the particle surface, promoting the formation of microspheres and increasing their mechanical strength. The adsorbent is prepared by grafting 4-vinylpyridine on cellulose microspheres, which is not only simple to synthesize, but also has strong adsorption capacity and good effect. In addition, it is easy to degrade and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the adsorption curve of each sample. DETAILED DESCRIPTION
[0022] The concept and technical effects of the present invention will be clearly and completely described below in conjunction with embodiments to fully understand the purpose, features and effects of the present invention.
[0023] Embodiment 1:
[0024] A composite microsphere adsorbent comprises, by weight, 1 part of cellulose, 0.05 part of a cross-linking agent, 1 part of silicon dioxide, 8 parts of 4-vinylpyridine, 16 parts of NaOH, 24 parts of urea, 168 parts of water, 212 parts of methanol, 100 parts of an emulsifier and 2000 parts of liquid paraffin.
[0025] The preparation method of the composite microsphere adsorbent described in this embodiment comprises the following steps, in parts by weight:
[0026] (1) 16 parts of NaOH and 24 parts of urea are dissolved in 160 parts of water and stirred to form a solution, which is then cooled to -15--9°C, cellulose and epichlorohydrin are added and stirred at 400 r / min for 30 min, and then centrifuged and degassed at 25°C and 5000 r / min for 30 min to obtain a transparent cellulose solution;
[0027] (2) Span 80 and nano-silica were added to liquid paraffin and ultrasonically stirred to disperse them uniformly, and then added to a transparent cellulose solution, stirred and emulsified at 25°C and 800 r / min for 3 hours, and then the pH was adjusted to 6.9-7.1 with dilute hydrochloric acid. After standing, the liquid was separated, the aqueous phase was filtered and washed twice with deionized water and acetone, and freeze-dried at -50--45°C for 24 hours to obtain cellulose / silica microspheres;
[0028] (3) 12 parts of methanol and 8 parts of water were mixed and 4-vinylpyridine was added and stirred to form a solution, and then cellulose / silica microspheres were added, and the oxygen in the solution was removed by nitrogen purge, vacuum paper was sealed and placed in a refrigerator to swell for 24 hours, and then sent to the cobalt source room for irradiation, with a dose rate of 20Gy / min and an absorbed dose of 20kGy. After irradiation, the sample was taken out, wrapped with filter paper and placed in a Soxhlet extractor, 200 parts of methanol were added for extraction for 24 hours, and then filtered and dried at 60°C in a vacuum oven for 24 hours to obtain a composite microsphere adsorbent.
[0029] Embodiment 2:
[0030] A composite microsphere adsorbent, whose raw materials, measured by weight, include: 1 part of cellulose, 0.075 parts of a cross-linking agent, 1.5 parts of silicon dioxide, 9 parts of 4-vinyl pyridine, 16 parts of NaOH, 24 parts of urea, 168 parts of water, 212 parts of methanol, 100 parts of an emulsifier, and 2000 parts of liquid paraffin.
[0031] The preparation method of the composite microsphere adsorbent described in this embodiment comprises the following steps, in parts by weight:
[0032] (1) 16 parts of NaOH and 24 parts of urea are dissolved in 160 parts of water and stirred to form a solution, which is then cooled to -15--9°C, cellulose and epichlorohydrin are added and stirred at 400 r / min for 30 min, and then centrifuged and degassed at 25°C and 5000 r / min for 30 min to obtain a transparent cellulose solution;
[0033] (2) Span 80 and nano-silica were added to liquid paraffin and ultrasonically stirred to disperse them uniformly, and then added to a transparent cellulose solution, stirred and emulsified at 25°C and 800 r / min for 3 hours, and then the pH was adjusted to 6.9-7.1 with dilute hydrochloric acid. After standing, the liquid was separated, the aqueous phase was filtered and washed twice with deionized water and acetone, and freeze-dried at -50--45°C for 24 hours to obtain cellulose / silica microspheres;
[0034] (3) 12 parts of methanol and 8 parts of water were mixed and 4-vinylpyridine was added and stirred to form a solution, and then cellulose / silica microspheres were added, and the oxygen in the solution was removed by nitrogen purge, vacuum paper was sealed and placed in a refrigerator to swell for 24 hours, and then sent to the cobalt source room for irradiation, with a dose rate of 20Gy / min and an absorbed dose of 20kGy. After irradiation, the sample was taken out, wrapped with filter paper and placed in a Soxhlet extractor, 200 parts of methanol were added for extraction for 24 hours, and then filtered and dried at 60°C in a vacuum oven for 24 hours to obtain a composite microsphere adsorbent.
[0035] Embodiment 3:
[0036] A composite microsphere adsorbent comprises, by weight, 1.1 parts of cellulose, 0.1 parts of a cross-linking agent, 2 parts of silicon dioxide, 10 parts of 4-vinylpyridine, 16 parts of NaOH, 24 parts of urea, 168 parts of water, 212 parts of methanol, 100 parts of an emulsifier and 2000 parts of liquid paraffin.
[0037] The preparation method of the composite microsphere adsorbent described in this embodiment comprises the following steps, in parts by weight:
[0038] (1) 16 parts of NaOH and 24 parts of urea are dissolved in 160 parts of water and stirred to form a solution, which is then cooled to -15--9°C, cellulose and epichlorohydrin are added and stirred at 400 r / min for 30 min, and then centrifuged and degassed at 25°C and 5000 r / min for 30 min to obtain a transparent cellulose solution;
[0039] (2) Span 80 and nano-silica were added to liquid paraffin and ultrasonically stirred to disperse them uniformly, and then added to a transparent cellulose solution, stirred and emulsified at 25°C and 800 r / min for 3 hours, and then the pH was adjusted to 6.9-7.1 with dilute hydrochloric acid. After standing, the liquid was separated, the aqueous phase was filtered and washed twice with deionized water and acetone, and freeze-dried at -50--45°C for 24 hours to obtain cellulose / silica microspheres;
[0040] (3) 12 parts of methanol and 8 parts of water were mixed and 4-vinylpyridine was added and stirred to form a solution, and then cellulose / silica microspheres were added, and the oxygen in the solution was removed by nitrogen purge, vacuum paper was sealed and placed in a refrigerator to swell for 24 hours, and then sent to the cobalt source room for irradiation, with a dose rate of 20Gy / min and an absorbed dose of 20kGy. After irradiation, the sample was taken out, wrapped with filter paper and placed in a Soxhlet extractor, 200 parts of methanol were added for extraction for 24 hours, and then filtered and dried at 60°C in a vacuum oven for 24 hours to obtain a composite microsphere adsorbent.
[0041] Comparative Example 1:
[0042] The difference between this comparative example and Example 1 is that nano silicon dioxide is not added in step (1), and the remaining raw materials and steps are the same as those in Example 1.
[0043] Comparative Example 2:
[0044] The difference between this comparative example and Example 1 is that 4-vinylpyridine is not added in step (1), and the remaining raw materials and steps are the same as those in Example 1.
[0045] Adsorbent performance test:
[0046] Mechanical strength test: The adsorbents prepared in Examples 1-3 and Comparative Examples 1-2 were placed in a compression testing machine, a certain pressure was applied, and the compression deformation and compression force of the adsorbent were measured, thereby calculating the mechanical strength of the adsorbent.
[0047] Table 1: Adsorbent strength test
[0048] Strength / MPa Example 1 3.11 Example 2 3.08 Example 3 3.36 Comparative Example 1 2.44 Comparative Example 2 3.17
[0049] It can be seen from the above table that the strength of Comparative Example 1 is lower than that of Example 1. This is because nano-silicon dioxide is not added in Comparative Example 1, while nano-silicon dioxide is added in Example 1. The surface of nano-silicon dioxide particles is negatively charged and will form hydrogen bonds with the hydrogen on the hydroxyl group in cellulose, so that cellulose is adsorbed on the surface of the particles, promoting the formation of microspheres and increasing their mechanical strength.
[0050] Heavy metal adsorption test: Take Cr(VI) as an example, and use a volumetric flask to prepare 1L of 100mg / L Cr(VI) adsorption solution for use.
[0051] Take 50 mg of each of the adsorbents prepared in Examples 1-3 and Comparative Examples 1-2 and place them in a 250 mL stoppered conical flask, and transfer 50 mL of the prepared Cr (VI) adsorption solution to each bottle. After plugging the bottle stopper, place it in a constant temperature oscillator for oscillation (20°C, 140 rpm). Take out the conical flask at different times (5, 10, 15, 20, 30, 40 and 60 min) and filter the adsorption solution with filter paper. The Cr (VI) concentration of the solution is determined by diphenylcarbazide spectrophotometry. The method is as follows: add 100 μL of the test solution, 0.5 mL of H2SO4 (1:1), 0.5 mL of H3PO4 (1:1) and 2 mL of 2 g / L diphenylcarbazide acetone aqueous solution (weight ratio 1:1) to a colorimetric tube (50 mL) in turn, shake well, and place for 10 minutes to wait for the color developer to fully develop color, and measure the absorbance of the solution at a wavelength of 540 nm using an ultraviolet spectrometer. The adsorption rate of Cr(VI) by the adsorbent was calculated based on the change of Cr(VI) concentration in the solution before and after adsorption.
[0052] Table 2. Adsorption statistics of each sample
[0053]
[0054] From Table 2 and Figure 1It can be seen that the absorption rate of Comparative Example 2 is poor. This is because 4-vinylpyridine is added in Comparative Example 2, and the unmodified natural cellulose only contains hydroxyl groups, and the adsorption performance of metals is not ideal. In Example 1, 4-vinylpyridine is grafted on the cellulose microspheres, which greatly improves its adsorption capacity and adsorption effect. In addition, Examples 1-3 can achieve an adsorption rate of 80% in 5 minutes, and the adsorption equilibrium is basically reached at 20 minutes. The time to reach the adsorption equilibrium is short, which shows its application potential in industrial production.
[0055] The above embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work shall all fall within the scope of protection of the present invention.
Claims
1. A composite microsphere adsorbent, characterized in that: The raw materials thereof include, by weight, 1-1.1 parts of cellulose, 0.05-0.1 parts of a cross-linking agent, 1-2 parts of silicon dioxide, 8-10 parts of 4-vinyl pyridine, 16 parts of NaOH, 24 parts of urea, 168 parts of water, 212 parts of methanol, 100 parts of an emulsifier, and 2000 parts of liquid paraffin.
2. A composite microsphere adsorbent according to claim 1, characterized in that: The cross-linking agent is epichlorohydrin.
3. The composite microsphere adsorbent according to claim 1, characterized in that: The emulsifier is Span 80.
4. The composite microsphere adsorbent according to claim 1, characterized in that: The silicon dioxide is nano silicon dioxide.
5. The method for preparing a composite microsphere adsorbent according to any one of claims 1 to 4, characterized in that: The steps include: (1) 16 parts of NaOH and 24 parts of urea are dissolved in 160 parts of water and stirred to form a solution, which is then cooled to -15--9°C, cellulose and a cross-linking agent are added and stirred at 400 r / min for 30 min, and then centrifuged and degassed at 25°C and 5000 r / min for 30 min to obtain a transparent cellulose solution; (2) adding an emulsifier and silicon dioxide to liquid paraffin and stirring the mixture ultrasonically to disperse the mixture uniformly, then adding the mixture to a transparent cellulose solution, stirring and emulsifying the mixture at 25° C. and 800 r / min for 3 h, and then adjusting the pH to 6.9-7.1 with dilute hydrochloric acid. After standing, the mixture is separated, the aqueous phase is filtered and washed twice with deionized water and acetone, and freeze-dried to obtain cellulose / silica microspheres; (3) 12 parts of methanol and 8 parts of water were mixed and 4-vinylpyridine was added and stirred to form a solution, and cellulose / silica microspheres were added. The oxygen in the solution was purged with nitrogen, and the solution was sealed with vacuum paper and placed in a refrigerator to swell for 24 hours, and then sent to the cobalt source room for irradiation. After the irradiation, the sample was taken out, wrapped with filter paper and placed in a Soxhlet extractor, and 200 parts of methanol were added for extraction for 24 hours, and then filtered and dried to obtain a composite microsphere adsorbent.
6. The method for preparing a composite microsphere adsorbent according to claim 5, characterized in that: The concentration of dilute hydrochloric acid in step (2) is 0.1 mol / L.
7. The method for preparing a composite microsphere adsorbent according to claim 5, characterized in that: The freeze drying in step (2) is performed at -50-45°C for 24 hours.
8. The method for preparing a composite microsphere adsorbent according to claim 5, characterized in that: The irradiation conditions in step (3) are a dose rate of 20 Gy / min and an absorbed dose of 20 kGy.
9. The method for preparing a composite microsphere adsorbent according to claim 5, characterized in that In step (3), the drying step is performed in a vacuum oven at 60°C for 24 hours.
Citation Information
Patent Citations
Cellulose base - silicon hybridization microsphere and preparation method thereof
CN102580691A
Difunctional cellulose based microsphere adsorbent and preparation method thereof
CN103962113A
Modified cellulose / graphene oxide composite microsphere and preparation method thereof
CN104226268A